Navigating State Administrative Decrees: Legal Strategies for Protecting Land Rights in Nusa Penida - Meisya, Tara; Haes, Putri Ekaresty (Universitas Negeri Gorontalo, 2025)
This writing focuses on providing legal assistance to the Nusa Penida community regarding land rights disputes, particularly those arising from a State Administrative decree. The activity involves analyzing State Administrative dispute cases to assess the impact of the decree on the community's land. Legal assistance is provided to enhance the community's understanding of the decree's implications and the steps they can take to assert their land rights. The methods used include case analysis, direct assistance, and field visits. The findings highlight the importance of raising legal awareness within the community and empowering them to actively fight for their land rights. Key actions include filing administrative objections and pursuing lawsuits in court when necessary. The intervention demonstrated how legal assistance can alleviate community concerns by offering clear, actionable steps to address the issues. This activity also underscores the complexity of land disputes in Nusa Penida, especially regarding pipil land, and the potential conflicts that may arise if these disputes are not resolved promptly and effectively.